Teachers’ Attitudes towards Inclusive Education - Faseeha Khursheed, Attiya Inam, Muhammad Abiodullah (JIE, 2024)
Inclusion involves the provision of a structured environment for students with special needs in general education classroom settings. Teachers are the fundamental pillar for the successful implementation of inclusive education. The study aimed to identify the cognitive, affective, and behavioral dimensions of teachers’ attitudes towards inclusive education.